Gridlock from diagnosis to treatment of multidrug resistant tuberculosis (MDR-TB) in Tanzania: patients' perspectives from a focus group discussion - Stellah G. Mpagama; Mangi J. Ezekiel; Peter M. Mbelele; Anna M. Chongolo; Gibson S. Kibiki; Kristen Petros de Guex; Scott K. Heysell (BMC, 2020)
Abstract Background Molecular diagnostics have revolutionized the diagnosis of multidrug resistant tuberculosis (MDR-TB). Yet in Tanzania we found delay in diagnosis with more than 70% of MDR-TB patients having a history of several previous treatment courses for TB signaling prior opportunities for diagnosis. We aimed to explore patients' viewpoints and experiences with personal and socio-behavioral obstacles from MDR-TB diagnosis to treatment in an attempt to understand these prior findings. Methods The study was conducted in December 2016 with MDR-TB patients admitted at Kibong'oto Infectious Diseases Hospital. A qualitative approach deploying focus group discussions (FGDs) was used to gather information. Groups were sex aggregated to allow free interaction and to gauge gender specific issues in the social and behavioral contexts. The FGDs explored pathways and factors in the service delivery that may have contributed in the delay in accessing MDR-TB diagnostics and/or treatment. Collected data were coded, categorized and thematically interpreted. Results Forty MDR-TB patients participated in six FGDs. Challenges and barriers contributing to the delay in accessing MDR-TB diagnosis to treatment were as follows: 1) Participants had a different understanding of MDR-TB that led to seeking services outside the conventional health system; 2) Socio-economic adversity made health-seeking behavior difficult and often unproductive; 3) In the health system, challenges included inadequacy of MDR-TB diagnostic centers, lack of knowledge on behalf of health care providers to consider MDR-TB and order appropriate diagnostics; 4) The specimen referral system for early diagnosis of MDR-TB was inefficient. Non-adherence of TB patients to first-line anti-TB drugs prior to MDR-TB diagnosis, given the multitude of barriers discussed, was coupled with both intentional and unintentional non-adherence of health care providers to international standards of TB care. Conclusion Patient-centered strategies bridging communities and the health system are urgently required for optimum MDR-TB control in Tanzania.